Percepción de los Estudiantes de Ingenierías del ITCR sobre la Apertura de una Maestría Interuniversitaria Semipresencial en Ingeniería Aeroespacial en Costa Rica - Rojas-Pérez, Sharon Paola (Instituto Tecnológico de Costa Rica, 2023)
This final graduation project has the main objective of knowing the perception of ITCR engineering students about a blended interuniversity master's degree in aerospace engineering in Costa Rica, as a basis for further research that considers the perception of engineering graduates in the field. country. Likewise, the focus of this research is mixed, its scope is descriptive, and the unit of analysis is the market study carried out on the active students of the Tecnologico de Costa Rica in computer engineering, electronics, industrial production, computers, design industrial, materials, physics, mechatronics, and industrial maintenance at the offices of Cartago, San Carlos, San José, Limón, and Alajuela. In addition, among the main results, it is found that most respondents are men, with an age range of 20 to 25 years, single, without children, Costa Rican, active TEC students in baccalaureate and undergraduate engineering programs in computing, electronics, mechatronics, and industrial production interested in the proposed master's degree. Finally, the main conclusion of this project is that the perception of the surveyed students was known, also that this study remains as a basis for future research expanding the population with graduates from different universities and that the interest in the proposed master's degree is positive and acceptance among surveyed engineering students.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2023.
Keywords: Oferta académica; Estudio de mercado; Ingeniería aeroespacial; Análisis de datos